ANALISIS YURIDIS TINDAK LANJUT PUTUSAN MAHKAMAH KONSTITUSI NOMOR 34/PUU-XI/2013 DENGAN SURAT EDARAN MAHKAMAH AGUNG NOMOR 7/2014 TENTANG PENINJAUAN KEMBALI - Fajri Yandi; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Constiutional Court issued decision Number 34/PUU-XI/2013 about the review that change the settings of the Relating Reconsideration in the code of criminal procedure by reason of justice in a criminal case , when found the existence of new circumstances (novum), then the restriction of PK contrary to the principles of justice that are so upheld by the judicial power to enforce the law and justice. The decision of the MK is then responded by the MA through the SEMA Number 7/2014 about the PK should only be submitted one time so that raises the conflict of how the legal certainty of the truth.The purpose of this study, to determine the basis of the follow-up to the verdict of MK Number 34/PUU-XI/2013, with the MA circular No. 7/2014 and to determine the juridical implication of the MA circular Number 7/2014 with the verdict of MK Number 34/PUU-XI/2013 as well as to know the theory of law whether the appropriate decision of the MK Number 34/PUU-XI/2013.This research was conducted using the normative approach, namely the principles of law, the type of data in this research is to use primary legal materials, namely the 1945 Constitution, secondary legal materials (books related to research results and data from the internet) and tertiary legal materials (Law Dictionary), data collection techniques in this research is literature study and the analysis of the data using the deductive method is to analyze the problems of the general form to a special shape.The results of the research are : First, the basis of the follow-up to the verdict of MK Number 34/PUU-XI/2013, with SEMA No. 7/2014 is a mistake because of the decision of the MK are final and are binding on all persons and legal entities that exist in Indonesia. Second, the implications of the SEMA Number 7/2014 with the verdict of MK Number 34/PUU-XI/2013 is unconstitutional because it resulted in a blurring of legal certainty. Third, in theory legislation MK decision Number 34/PUU-XI/2013 is not appropriate in the follow-up with SEMA Number 7/2014 because SEMA is a regulatory policy. The author's suggestion, First, expected MA revoke SEMA Number 7/2014 to respect the decision of MK Number 34/PUU-XI/2013 for the sake of legal certainty and justice. Second, the legislation is expected to dig in and do a discovery of the law better longer based on a sense of justice and expediency according to the constitutional. Third, for the Country is expected to be able to evaluate the provisions of the norms or regulations that will be issued if entry laws and regulations.Key words: Analysis of Juridical - The Decision Of The Constitutional Court - Circular of The Supreme Court of Indonesia Number 7/2014